Significant Differences in Markers of Oxidant Injury between Idiopathic and Bronchopulmonary-Dysplasia-Associated Pulmonary Hypertension in Children - Kimberly B. Vera; Donald Moore; English Flack; Michael Liske; Marshall Summar (Pulmonary Medicine)
While oxidant stress is elevated in adult forms of pulmonary hypertension (PH), levels of oxidant stress in pediatric PH are unknown. The objective of this study is to measure F2-isoprostanes, a marker of oxidant stress, in children with idiopathic pulmonary hypertension (IPH) and PH due to bronchopulmonary dysplasia (BPD). We hypothesized that F2-isoprostanes in pediatric IPH and PH associated with BPD will be higher than in controls. Plasma F2-isoprostanes were measured in pediatric PH patients during clinically indicated cardiac catheterization and compared with controls. F2-Isoprostane levels were compared between IPH, PH due to BD, and controls. Five patients with IPH, 12 with PH due to BPD, and 20 control subjects were studied. Patients with IPH had statistically higher isoprostanes than controls 62 pg/mL (37–210) versus 20 pg/mL (16–27), 𝑃<0.01). The patients with PH and BPD had significantly lower isoprostanes than controls 15 pg/mL (8–17) versus 20 pg/ml (16–27), 𝑃<0.02. F2-isoprostanes are elevated in children with IPH compared to both controls and patients with PH secondary to BPD. Furthermore, F2-isoprostanes in PH secondary to BPD are lower than control levels. These findings suggest that IPH and PH secondary to BPD have distinct mechanisms of disease pathogenesis.